Triple-element stable isotope analysis of chloromethane emitted by royal fern and degraded by club moss - Hartmann, Simon Christoph; Keppler, Frank; Greule, Markus; Lauer, Rebekka; Horst, Axel (Journal of geophysical research. Biogeosciences, 2023)
Chloromethane (CH3Cl) is the most abundant natural chlorinated organic compound in the atmosphere playing an important role in catalyzing stratospheric ozone loss. Vegetation emits the largest amounts of CH3Cl to the atmosphere but its source strength is highly uncertain leading also to large uncertainties in the global budget of CH3Cl. Triple-element stable isotope analysis may help to reduce uncertainties because it provides additional process-level information compared to conventional quantification methods. In this study we performed experiments to obtain a first triple-elemental isotopic fingerprint (2H, 13C, 37Cl) of CH3Cl emitted by a relevant plant species (royal fern, Osmunda regalis). Isotopic values of all three elements showed considerable differences compared to isotopic values of industrially manufactured CH3Cl which bodes well for future applications to distinguish individual sources. Isotopic analysis of potential precursors (rain, methoxy groups) of CH3Cl in plants revealed no measurable change of hydrogen and chlorine isotopic ratios during formation which may provide a simpler route to estimate the isotopic composition of CH3Cl emissions. Plant degradation experiments of CH3Cl were carried out with club moss (Selaginella kraussiana) revealing significant isotopic fractionation for all three elements. The fractionation pattern characterized by epsilon and lambda is inconsistent with known biotic dechlorination reactions indicating a yet unreported biotic degradation mechanism for CH3Cl. Overall, this study provides first insights into the triple-elemental isotopic fingerprint of plant emissions and degradation. The results may represent important input data for future isotope-based models to improve global budget estimates of CH3Cl and to explore the yet unknown degradation pathways.